When China Rules the World : The End of the Western World and the Birth of a New Global Order - Jacques, Martin (London Penguin Book, 2012)
China will replace the United States as the world's dominant power. In so doing, it will not become more western but the world will become more Chinese. This title introduces a set of ideas including China as a civilization-state, the tributary system, the Chinese idea of race, and the principle of contested modernity.
Include Notes, Bibliography and Index
Keywords: Economic history -- China -- Globalization--Economic aspects